2018
DOI: 10.4269/ajtmh.17-0143
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Nutritional and Health Status in School Children from the Highlands and Lowlands of Bolivia

Abstract: Children in the Bolivian Andes are exposed to endemic infections and meager nourishment, and live under poor hygienic conditions. The prevention of children malnutrition is a priority in many countries including Bolivia. In this study, the health status of schoolchildren in Taraco, a Puna district, at 4,000 meters above sea level (masl) and in Caranavi, at 650 masl in the wealthier subtropical valleys, was compared. The weight, height, and hematological and biochemical parameters in blood, parasites in stool, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Poor hygiene conditions in communities of Bolivia highlands showed a greater prevalence of malnutrition and anemia, while children in the lowland population showed more overweight or obesity (Teran et al 2018). Another study revealed more than double the cases of anemia in the highland rural areas than those in the lowlands (Garrido-Salazar et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Poor hygiene conditions in communities of Bolivia highlands showed a greater prevalence of malnutrition and anemia, while children in the lowland population showed more overweight or obesity (Teran et al 2018). Another study revealed more than double the cases of anemia in the highland rural areas than those in the lowlands (Garrido-Salazar et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Evidence is scarce on the influence altitude on the growth of children in Ethiopia, albeit it bears one of the largest global highland populations as well as a great variation in residential altitude (20) . Other countries with a large highland population and varying residential altitude include Tibet (China), Nepal, Colombia, Bolivia, Peru, Kazakhstan, Bolivia, Argentina, Bhutan and Switzerland (7,8,13) . Our finding of high growth faltering at high altitude was consistent with the findings of previous studies done in these highland countries.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of stunting among Tibetan children residing in highlands was two to six times higher, compared with those residing in lowlands (9) . In Bolivia, the prevalence of stunting was six times higher in highlands than in lowlands (7,26) . In Argentina, the risk of stunting was twice higher in highlands than in lowlands (8) .…”
Section: Discussionmentioning
confidence: 99%
“…A study of 236 Bolivian children in lowlands (650 m) and highlands (4000 m), who had poor hygiene and nourishment, as well as endemic infections, found a slightly higher prevalence of vitamin D deficiency in the highlands group; the proportion in both groups was approximately 60%. (86) A sample of 1222 children from two locations above 1000 m in Himachal Pradesh, India, showed a deficiency of approximately 80%. (87) Latitude Higher latitudes are associated with larger SZAs that result in lower total UVB irradiances but with an increased diffuse component caused by UVR scattering and decreased vitamin Deffective UVB.…”
Section: Atmospherementioning
confidence: 99%